INVESTIGATION OF RAIN-INDUCED SIGNAL ATTENUATION FOR SATELLITE COMMUNICATION IN ABUJA AND KADUNA, NIGERIA - Modibbo, Aishat Al-Tine; Tyabo, A. M.; Gyuk, Philip Musa; Ladan, Muhammad Bello; Ndonya, Atsacha Ishaku; Bashir, M. A.; Usman, C. (FUDMA Journal of Sciences, 2025)
This paper examines rain-induced attenuation on Ku-band (12 GHz and 14 GHz) satellite communication links over Abuja and Kaduna, Nigeria, using three years (2022–2024) of rainfall data from the Nigerian Meteorological Agency (NiMet). The Lavergnat–Gole (LG) model was employed to derive 1-minute rain rates and corresponding attenuation for both horizontal and vertical polarisations. Results revealed rainfall rates of 95.90 mm/h in Abuja and 107.01 mm/h in Kaduna exceeded for 0.01% of the time, showing stronger rainfall intensity in Kaduna. Attenuation increased with frequencies, path length and horizontal polarisation, with Kaduna experiencing higher signal losses ranging from 15.36 dB to 152.86 dB compared to Abuja with values 13.56 dB to 134.82 dB and vertical polarization 11.95 dB to 118.89 dB in Kaduna compared to 10.63 db to 105.73 dB in Abuja at 14 GHz while horizontal polarisation for Kaduna values ranges from 11.99 dB to 119.36 dB compared to 10.54 dB to 104.79 dB in Abuja and vertical polarization for Kaduna values ranges from 8.21 dB to 92.43 dB compared to Abuja with values ranging from 8.21 dB to 81.69 dB at 12 GHz operational frequencies for path-length of 2 km, 5 km, 10 km, 15 km and 20 km link. The study concludes that rain attenuation critically limits Ku-band reliability in tropical regions, and recommends sufficient fade margin and adaptive power control to enhance system performance.